Disciplinamiento de las subjetividades como estrategia de prevención de incendios: El caso de las plantaciones forestales en el sur de Chile - González Hidalgo, Marien (2018)
The establishment of the Chilean forestry model based on monocultures of fast-growing species was possible not only thanks to the concentration of land and public-private investments to establish an extractive industry aimed towards export, but also through a shift in fire use in the territory. This article reviews the historical role of fire in the establishment of forestry extractivism in southern Chile. Foucault’s notion of discipline is useful in explaining how the exclusion of the use of fire was and is discursively supported, by means of the dissemination of environmental messages to local populations, while state and private capital favor the expansion of tree plantations with severe socio-environmental impacts for local communities. In this article I show how fire prevention campaigns seek to establish and subjective and emotional discipline that guarantees the accumulation of capital associated with forest extractivism.